Gene therapy shines light on congenital stationary night blindness for future cures - Yi Zhang; Siqi Lin; Lingqi Yu; Xiang Lin; Shuai Qu; Qingyang Ye; Mengting Yu; Wenfeng Chen; Wenjie Wu (Journal of Translational Medicine)
Abstract Congenital Stationary Night Blindness (CSNB) is a non-progressive hereditary eye disease that primarily affects the retinal signal processing, resulting in significantly reduced vision under low-light conditions. CSNB encompasses various subtypes, each with distinct genetic patterns and pathogenic genes. Over the past few decades, gene therapy for retinal genetic disorders has made substantial progress; however, effective clinical therapies for CSNB are yet to be discovered. With the continuous advancement of gene-therapy tools, there is potential for these methods to become effective treatments for CSNB. Nonetheless, challenges remain in the treatment of CSNB, including issues related to delivery vectors, therapeutic efficacy, and possible side effects. This article reviews the clinical diagnosis, pathogenesis, and associated mutated genes of CSNB, discusses existing animal models, and explores the application of gene therapy technologies in retinal genetic disorders, as well as the current state of research on gene therapy for CSNB. Graphical abstract